Gaps in DNA-Based Biomonitoring Across the Globe - McGee, Katie M.; Robinson, Chloe V.; Hajibabaei, Mehrdad (Frontiers in Ecology and Evolution, 2019)
DNA-based methodology has proven to be a vital tool for ecosystem assessment and monitoring. Increasingly, high-throughput approaches such as DNA metabarcoding are being used to address more complex questions, including ecological network analyses through machine learning. Despite the technological advances which allow for such questions to be posed, there remains inherent limitations in studies utilizing DNA metabarcoding, referring to environmental sample type targeted, geographical coverage and lack of standardised field and laboratory procedures. Additionally, DNA reference databases are lacking information from taxa, resulting in unidentified sequences and underrepresentation of some taxa. These issues need to be addressed to enable a more representative approach to ecosystem monitoring to allow for detection and monitoring of global ecosystem change.